Pengelolaan Perpustakaan Keliling di Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Sumatera Barat - Riska Dewita; Malta Nelisa (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
This article aims to describe: (1) management of mobile libraries in the Regional Office of the Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Sumatera Barat; (2) constraints and efforts in the management of the mobile library at the Regional Office of the Ministry of Justice and Human Rights of West Sumatra. Data collected by observation and interviews with the two (2) people bookmobile librarian in the management of the Regional Office of the Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Sumatera Barat. Based on the discussion can be summarized as follows: (1) management of mobile libraries in the Regional Office of the Kantor Wilayah Kementerian Hukum and Hak Asasi Manusia Sumatera Barat has not run as it should; (2) difficulties in the management of the mobile library at the Regional Office of the Kementerian Hukum and Asasi Manusia Sumatera Barat is the lack of library materials in the management of mobile libraries, library infrastructure is not yet fully support the activities of the management of the mobile library. Efforts made in overcoming obstacles as follows: add library materials will be lent to userlibrary, overcoming the lack of infrastructure as soon as possible, improve the service system will be given to userlibrary and add insight of human resources in order to increase the knowledge of librarians in the management of the mobile library. Keywords: management, library, roving.